Disturbance of Microbial Core Species in New-Onset Juvenile Idiopathic Arthritis - Hissink Muller, Petra; de Meij, Tim G.J.; Westedt, Michiel; de Groot, Evelien F.J.; Allaart, Cornelia F.; Brinkman, Danielle M.C.; Schonenberg-Meinema, Dieneke; van den Berg, Merlijn; van Suijlekom-Smit, Lisette W.A.; Rossum, Marion van; Budding, Andries E.; ten Cate, Rebecca (Journal of Pediatric Infectious Diseases, 2017)
Over the past decades, the intestinal microbiota has increasingly gained attention in studies addressing the pathophysiology of (pediatric) autoimmune diseases, including inflammatory joint diseases, inflammatory bowel disease (IBD), and type 1 diabetes. In this study, we have analyzed the composition of gut microbiota of newly diagnosed juvenile idiopathic arthritis (JIA) patients, prior to initiation of disease-modifying antirheumatic drugs (DMARDs). Fecal microbiota profiles of 8 JIA patients (median age: 11.1 years, 6 girls) were compared with 22 healthy age-matched controls using IS-pro, a 16S-23S interspacer (IS) region-based, eubacterial molecular detection technique. By partial least squares discriminant analysis (PLS-DA), microbiota profiles of JIA and controls could significantly be discriminated based on a limited set of species belonging to the phylum Bacteroidetes (Fig. 2), but not within other phyla, with a sensitivity of 88%, specificity of 73% (Fig. 3), and area under the curve (AUC) 0.87 (95% CI: 0.73–0.87). These discriminative species have been considered to be part of the microbial core in healthy children.Conclusion Our findings add to the increasing notion that the gut microbiota may be involved in the pathophysiology of JIA. Species involved in the discrimination between JIA and controls are members of the microbial core in the healthy state. Expanding knowledge on JIA-specific microbial signatures and host interactions may open avenues to explore options to develop individualized, microbiota-based preventive, and therapeutic interventions in JIA.
Keywords: autoimmunity; juvenile idiopathic arthritis; intestinal microbiota; gut; IS-pro